Efektivitas Bimbingan Kelompok Menggunakan Pendekatan Behavioral Therapy Untuk Meningkatkan Rasa Percaya Diri Pada Remaja Introvert - Syahfitri, Wardana; Hasibuan, Uli Makmun; Arista, Nadia; Zakia, Raudatul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research was taken based on the current number of teenagers who have introverted personalities. This introverted personality is caused by low self- confidence, it is difficult to adapt to the surrounding environment and these teenagers have a high fear of speaking, it is not uncommon for these teenagers to doubt their abilities and always think that they will not be able to do something. This research The aim is to find out the benefits of group guidance, which uses a behavioral therapy approach to increase self-confidence in teenagers who have introverted personalities. The method used is Systematic Literature Review (SLR), namely by combining references from various analytical journals, data using a qualitative meta-synthesis approach, namely a method that identifies and evaluates research results according to research questions, topics or events that are discussed.